DETERMINATION OF HEAVY METAL CONTENTS IN FLUTED PUMPKIN LEAVES (TELFAIRIA OCCIDENTALIS) ALONG ROADSIDES IN CALABAR, NIGERIA - Akpan Ita Okon; William Eddy Sunday; Inyang Ephraim Peter (European Scientific Journal, ESJ, 2015)
Particle Induced X-ray Emission (PIXE) spectrometry was used for the analysis of elemental contents in the leaves of fluted pumpkin (Telfairia Occidentalis) grown along roadsides in Calabar for the purpose of ascertaining the levels of heavy metals. Seventeen elements, viz., Mg, Al, Si, P, S, Cl, K, Ca, Ti, Cr, Mn, Fe, Ni, Cu, Zn, Rb, and Sr with concentration ranging from 1.2±3.3 (Zn) to 56562.8±118.8 ppm (K) were detected from ten different sample locations. Concentrations of these elements reveals that areas with the highest number of vehicles plying sample locations recorded highest levels of heavy metals compared to areas with low traffic density. Elements such as Mn/Cu (0.754), Cu/Zn (0.820), Al/Mn (0.658), Al/Cu (0.640), and Ti/Fe (0.653) had strong, positive, and significant correlation corroborating the results of the enrichment factor, cluster analysis, and vehicular count. This confirmed that the presence of heavy metals in fluted pumpkin leaves on roadsides in Calabar is associated with vehicular emission.